1992
DOI: 10.2307/2111485
|View full text |Cite
|
Sign up to set email alerts
|

International Events and Foreign Policy Beliefs: Public Response to Changing Soviet-U.S. Relations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. How do citizens respond to dramatic foreign policy events, such as the recent changes in Soviet-U.S. relations, when a traditional foe exhibits strong signs of conciliatory be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 51 publications
4
98
1
1
Order By: Relevance
“…Hurwitz and Peffley, in accordance with the pathbreaking work on core values by Feldman & Zaller (1992), argued that ethnocentrism and the morality of warfare were the core values that shaped people's opinions about certain approaches to foreign affairs, which in turn determined the level of support or opposition to specific foreign policy actions (Hurwitz & Peffley 1987a, Peffley & Hurwitz 1992. A related strand of research indicated that personality characteristics, such as aggression or accommodation, contributed to preference formation on a variety of international security and trade policies (Herrmann et al 1999, Herrmann et al 2001.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hurwitz and Peffley, in accordance with the pathbreaking work on core values by Feldman & Zaller (1992), argued that ethnocentrism and the morality of warfare were the core values that shaped people's opinions about certain approaches to foreign affairs, which in turn determined the level of support or opposition to specific foreign policy actions (Hurwitz & Peffley 1987a, Peffley & Hurwitz 1992. A related strand of research indicated that personality characteristics, such as aggression or accommodation, contributed to preference formation on a variety of international security and trade policies (Herrmann et al 1999, Herrmann et al 2001.…”
mentioning
confidence: 99%
“…Zaller posits that survey answers are a "top-of-the-head" response to the questions presented. These answers reflect a person's beliefs (not unlike the "core values" of Feldman & Zaller 1992, Hurwitz & Peffley 1987a, and Peffley & Hurwitz 1992), but they also reflect the considerations that happen to be salient to the respondent at the moment the question is posed. Responses to any one question may not reflect the full complexity of an underlying attitude.…”
mentioning
confidence: 99%
“…Accordingly, public opinion on defence and foreign affairs possesses structure and responds reasonably to foreign policy events (e.g. Peffley and Hurwitz, 1992;Shapiro and Page, 1988;Isernia et al, 2002). Thus, elites have an incentive to respond to public preferences in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The literature demonstrates that public opinion in both the United States and Western Europe responds to the external environment and foreign policy change in a continuously coherent, systematic way (Eichenberg, 1989;Holsti, 1996;Nincic, 1988;Peffley & Hurwitz 1992;Shapiro & Page 1988) (Note 1). With defense spending a more salient issue to the public than foreign policy in general, the public in these countries has adjusted its preference for more or less defense spending in response to defense than most of its allies, while Britain has shouldered its share of the defense burden larger than any other European NATO partner.…”
mentioning
confidence: 99%